Generation of ‘Immigrant’ Generations - Calabretta, Andrea; Della Puppa, Francesco; Ragone, Marianna (Italian Sociological Review, 2025)
In addition to the age factor and the way in which the passage of time and history can be seen as a succession of generations, the concept of generation must also be thought of as a mode of classification that is necessarily contested. Immigration poses a question of generation that is special in that it, firstly, involves the addition of an external factor in the evolution of a society and, secondly, involves the creation of a new type of generational identification within that society. The social milieu of immigrants therefore represents a laboratory where all the latent meanings engendered by the relationships between the individuals and the group and between the different generations may be studied.